Effects of a Novel Estrogen-Free, Progesterone Receptor Modulator Contraceptive Vaginal Ring on Inhibition of Ovulation, Bleeding Patterns and Endometrium in Normal Women - Croxatto -Avoni, H (2012)
Background: Progesterone receptor modulators (PRMs) delivered by contraceptive vaginal rings provide an opportunity for development of an estrogen-free contraceptive that does not require daily oral intake of steroids. The objective of this proof-of-concept study was to determine whether continuous delivery of 600-800 mcg of ulipristal acetate (UPA) from a contraceptive vaginal ring could achieve 80% to 90% inhibition of ovulation. Study Design: This was a prospective, controlled, open-labeled, multicenter international trial to examine the effectiveness and safety of this prototype vaginal ring. Thirty-nine healthy women, 21-40 years old and not at risk of pregnancy, were enrolled at three clinic sites. Volunteers participated in a control cycle, a 12-week treatment period and a post-treatment cycle. Pharmacodynamic effects on follicular function and inhibition of ovulation, effects on endometrium, bleeding patterns and serum UPA levels were evaluated. Results: Mean UPA levels during treatment were nearly constant, approximately 5.1 ng/mL throughout the study. Ovulation was documented in 32% of 111 "4-week treatment cycles." A correlation was observed between serum UPA and degree of inhibition of ovarian activity. There was no evidence of hyperplasia of endometrium, but PRM-associated endometrial changes were frequently observed (41%). Conclusion: In this study, the minimum effective contraceptive dose was not established. Further studies are required testing higher doses of UPA to attain ovulation suppression in a higher percentage of subjects. © 2012 Elsevier Inc.